Fine‐needle aspiration cytology for the diagnosis of plasma cell neoplasms in the head and neck region: A systematic analysis of the literature. Issue 3 (28th December 2022) - Felix, Fernanda Aragão; de Sena, Ana Carolina Velasco Pondé; de Arruda, José Alcides Almeida; Tavares, Thalita Soares; Rocha, Amanda Leal; Rodrigues‐Fernandes, Carla Isabelly; de Cáceres, Cinthia Verónica Bardález López; Vargas, Pablo Agustin; Abreu, Lucas Guimarães; Amaral, Tania Mara Pimenta; Travassos, Denise Vieira; de Sousa, Silvia Ferreira; et al.
Abstract: Background: Cytopathologic analysis is feasible and provides detailed morphological characterisation of head and neck lesions. Aims: To integrate the available data published on fine‐needle aspiration cytology (FNAC) used for the diagnosis of plasma cell neoplasms (PCN) of the head and neck region. Materials and Methods: Searches on PubMed, Web of Science, Embase, and Scopus were performed to compile data from case reports/case series published in English. The Joanna Briggs Institute tool was used for the critical appraisal of studies. Results: A total of 82 studies comprising 102 patients were included in this review. There was a predilection for men (68.6%) (male/female ratio: 2.1:1). Individuals in their 50s (29.4%), 60s (22.5%), and 70s (22.5%) were more often affected. The thyroid gland (26.2%) was the main anatomical location, followed by scalp (15.5%), neck/cervical region (15.5%), jaws (13.6%), and major salivary glands (13.6%). For FNAC analysis, a smear was employed in 41 (40.6%) cases and a cell block was used in four (3.9%). In 56 (55.4%) reports, no cytological methods were available. Morphologically, 34 (56.7%) cases had a diagnosis of PCN with agreement between cytopathology and histopathology. The rate of wrong diagnoses when using cytology was 27.5%. Immunophenotyping was performed in 49 (48%) of the cases. The 69‐month disease‐free survival rate was 60.2%, while the 27‐month overall survival rate was 64.1%. Conclusion: This study reinforces that FNAC can be an ancillary tool in the first step towards the diagnosis of PCN of the head and neck region, especially when applying a cell block for cytological analysis.